Alley cropping system improves forage productivity and profitability in rainfed semi-arid Rajasthan - Choudhary, Mukesh; Kantwa, S.R.; Dixit, A.K.; Nagar, R.P. (Indian Journal of Agroforestry, 2020)
Scarcity of green fodder is a major constraint for low productivity of livestock in arid and semi-arid regions of Rajasthan. Fodder availability can be increased particularly in lean periods through planting of shrubs and grasses in alley cropping systems with traditional crops. A field experiment was conducted during 2016-18 to identify suitable perennial shrub and grass which can grow under high temperature and low soil moisture availability conditions. Sesbania sesban and Cenchrus ciliaris were identified and four alley cropping systems were formulated and tested with pearl millet and clusterbean for fodder productivity and profitability in randomized block design. S. sesban + C. ciliaris + pearl millet (F) cropping system recorded significantly higher system productivity (32.9 t/ha green fodder equivalent yield) which was 47.5 and 35.4% higher in comparison to sole cropping of pearl millet and clusterbean, respectively. Higher net returns (Rs. 19542/ha) and benefit: cost ratio (1.98) were also recorded in this treatment. Thus, based on the results, S. sesban + C. ciliaris + pearl millet (F) alley cropping systems can be suggested for higher forage productivity and profitability in rainfed semi-arid regions.